2020
DOI: 10.1186/s12937-020-00622-z
|View full text |Cite
|
Sign up to set email alerts
|

Modern dietary pattern is prospectively associated with earlier age at menarche: data from the CHNS 1997–2015

Abstract: Background Early age at menarche is associated with risk of several chronic diseases. Prospective study on the association between dietary pattern and timing of menarche is sparse. We examined whether dietary patterns prior to the menarche onset were prospectively associated with menarcheal age in Chinese girls. Methods One thousand one hundred eighteen girls aged 6–13 y in the China Health and Nutrition Survey (CHNS) with three-day 24-h recalls and information on potential confounders at baseline were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Factor loadings reflect the correlations of each food group with the corresponding dietary pattern. Food groups with factor loadings ≥0.30 or ≤ −0.30 were considered as the most important contributors to each factor ( 33 ), and thus descriptive of that dietary pattern. Furthermore, the factor score for each pattern was constructed by summing standardized intakes of each food group weighted by their factor loadings, so that higher factor scores indicated better adherence to dietary patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Factor loadings reflect the correlations of each food group with the corresponding dietary pattern. Food groups with factor loadings ≥0.30 or ≤ −0.30 were considered as the most important contributors to each factor ( 33 ), and thus descriptive of that dietary pattern. Furthermore, the factor score for each pattern was constructed by summing standardized intakes of each food group weighted by their factor loadings, so that higher factor scores indicated better adherence to dietary patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we were not able to include the information on body weight or nutrition status at adolescents even though we suggested underweight as a key factor. Particularly, a dietary pattern is an important confounding factor for the association between reproductive factor and CVD, which could not be considered on this study [ 46 48 ]. Further studies including such confounding factor are needed.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we only found one study that longitudinally evaluated dietary patterns and age at menarche. Duan et al ( 53 ) found in Chinese girls, a sample with high adherence to “Modern” dietary patterns, was associated with higher odds of experiencing menarche at an earlier age. Taken together, this evidence suggests that unhealthy dietary patterns have a potential influence on pubertal timing through metabolic changes in insulin-mediated pathway mechanisms and the upregulation of hormones ( 21 ).…”
Section: Discussionmentioning
confidence: 99%